Reality Group Counseling to Reduce Phubbing Behavior in College Students - Irma Suryani Nasution; Silvianetri; Darimis; Irman; Wahidah Fitriani; Ardimen (Bisma The Journal of Counseling, 2025)
The background of this study is the high prevalence of phubbing behavior, which has a negative impact on college students' social interactions. Through reality group counseling, external control behavior can be changed to internal control behavior, resulting in pleasure and enjoyment in life. This study aims to analyze the effectiveness of reality group counseling in reducing phubbing behavior among college students. A quantitative approach with a quasi-experiment using a pretest-posttest control group design was used. Data were collected using a phubbing behavior scale. The scale used in this study was the phubbing behavior scale for college students. This study involved a population of 37 students and a sample of 16 students. The sampling technique was done randomly. Data analysis was performed using an independent samples t-test, while the n-gain test was applied to assess the effectiveness of the intervention. Phubbing behavior was reduced through reality group counseling using the WDEP technique, which was conducted over 8 sessions, followed by a posttest using the phubbing behavior scale. The findings indicate that reality group counseling effectively reduces phubbing behavior, as shown by the results of an independent t-test of 0.000 < 0.05. The effectiveness of reality group counseling was 77.5%, indicating a significant impact on college students with high levels of phubbing behavior. These findings emphasize the importance of managing technology use and increasing direct social interaction in order to improve the quality of interpersonal relationships.